GIRILOYO WRITTEN BATIK MOTIFS VIEWED FROM AN ETHNOMATHEMATICS PERSPECTIVE - Abdullah, Ahmad; Richardo, Rino; Mubarok, Muhammad Najib; Bayu, Widya Sekar (Jurnal Math-UMB.EDU, 2024)
School mathematics which is often studied is generally formal, rigid and strict. Students still experience difficulties in applying mathematical concepts in everyday life. The results of PISA of Indonesia 2023 show that the mathematical literacy skills of Indonesian students are currently still relatively low. The independent curriculum provides flexibility for teachers to develop mathematical literacy skills with innovative mathematics learning models based on real life contexts, one of which is culture. Ethnomathematics as a research study that links culture and mathematics. The aim of this research is to find out the results of an ethnomathematics study on giriloyo batik motifs, especially on sidomukti, sidoluhur and sidoasih motifs. This type of research is qualitative research with an ethnographic approach. The methods used for data collection are interviews, observation and documentation. The results of this research showed that the giriloyo batik motif contains the concept of geometric transformation in the form of reflection. Keywords: Ethnomathematics, Written Batik, Geometric Transformation